WEBSITE PARAMITA MEMBER CLUB DENGAN MENERAPKAN MODEL AFFILIATE MARKETING - Safitri, Ayu; ., Sujito (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
Member Club Website Paramita affiliate marketing by applying the model was built with the aim to extend the range of netting prospective freshmen. The method used in this study is the method of data collection and system development methods. In the method of data collection conducted the interview on the new admissions as well as library research done either through library research results of previous studies, related literature and research records and documents relating to the research firm. System development method used is method SDLC (System Development Life Cycle) with the stages that include system analysis, system design, implementation and operation and maintenance. Of research has been done can be obtained form the website awakening Paramita Member Club that implement affiliate marketing models and implemented database system on the website Paramita Member Club as an alternative to extend the range of netting new students in Malang STMIK PPKIA Pradnya Paramita. Keywords: Website, Affiliate Marketing